Peran Suhu Makanan pada Sisa Makanan Pokok, Lauk Hewani, Lauk Nabati dan Sayur pada Pasien Diet TKTP - Metta Paramita; Hapsari Sulistya Kusuma (Jurnal Gizi, 2020)
Food temperature is one of the factors that influence the occurrence of leftovers in patients, one of them is a patient in the hospital. This study aims to determine the relationship of food temperature with food waste in adult patients.This type of research is observation using a survey method with cross-sectional approach. The population of all adult patients at Roemani Muhammadiyah Hospital Semarang City who were on the TKTP diet were 32 people and the sample was selected with inclusion criteria, namely adult patients aged 19-55 years old, no nausea, vomiting and getting TKTP diet while exclusion criteria were patients completed treatment and the presence of food diet changes. Analysis of corellation using Pearson correlation test.Of the total sample of 24people 50% aged 31-40 years, 83.3% were female, 66.7% had the last high school education, 66,7% were diagnosed with medical post partum. The results of data analysis of the relationship between food temperature and staple food scraps, animal side dishes, vegetable side dishes and vegetables arer = -0.42 p value 0.041, r = -0,005 p value 0.98, r = 0, 09 p value 0.67,r = -0.49 p value 0.014. It was concluded that there is a relationship between food temperature and the rest of the menu of staple food and vegetables and there is no relationship between the temperature of the food with the rest of the menu of animal and vegetable side dishesKeywords: Food Temperature, Leftovers, TKTP Diet